Interactive effects of music and prefrontal cortex stimulation in modulating response inhibition. Issue 1 (December 2017) - Mansouri, Farshad; Acevedo, Nicola; Illipparampil, Rosin; Fehring, Daniel; Fitzgerald, Paul; Jaberzadeh, Shapour
Abstract Influential hypotheses propose that alterations in emotional state influence decision processes and executive control of behavior. Both music and transcranial direct current stimulation (tDCS) of prefrontal cortex affect emotional state, however interactive effects of music and tDCS on executive functions remain unknown. Learning to inhibit inappropriate responses is an important aspect of executive control which is guided by assessing the decision outcomes such as errors. We found that high-tempo music, but not low-tempo music or low-level noise, significantly influenced learning and implementation of inhibitory control. In addition, a brief period of tDCS over prefrontal cortex specifically interacted with high-tempo music and altered its effects on executive functions. Measuring event-related autonomic and arousal response of participants indicated that exposure to task demands and practice led to a decline in arousal response to the decision outcome and high-tempo music enhanced such practice-related processes. However, tDCS specifically moderated the high-tempo music effect on the arousal response to errors and concomitantly restored learning and improvement in executive functions. Here, we show that tDCS and music interactively influence the learning and implementation of inhibitory control. Our findings indicate that alterations in the arousal-emotional response to the decision outcome might underlie these interactive effects.